2010
DOI: 10.1016/j.econmod.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the use of vignettes in cross-country health studies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…The lack of a significant effect of age on SRH is surprising, though consistent with—indeed, caused by—the earlier finding that older respondents are more health-pessimistic (and so have self-ratings adjusted upwards by chopit). Datta Gupta, Kristensen, and Pozzoli (2010), analyzing disability vignettes, report very similar findings, which they show result from age-related response in consistency—the failure of respondents to treat vignette characters as age peers. Our vignettes appear to suffer the same problem (a possibility supported by survey audio recordings in which respondents ask the vignette characters’ ages) 8.…”
Section: Resultsmentioning
confidence: 82%
“…The lack of a significant effect of age on SRH is surprising, though consistent with—indeed, caused by—the earlier finding that older respondents are more health-pessimistic (and so have self-ratings adjusted upwards by chopit). Datta Gupta, Kristensen, and Pozzoli (2010), analyzing disability vignettes, report very similar findings, which they show result from age-related response in consistency—the failure of respondents to treat vignette characters as age peers. Our vignettes appear to suffer the same problem (a possibility supported by survey audio recordings in which respondents ask the vignette characters’ ages) 8.…”
Section: Resultsmentioning
confidence: 82%
“…On vignette equivalence, see Murray et al (2003), Kristensen and Johansson (2008), Bago d’Uva et al (2011) and Rice et al (2011). On response consistency, see van Soest et al (2011), Bago d’Uva et al (2011) and Datta Gupta et al (2010).…”
Section: Joint Model Of Visits To a Doctor And Health Reportingmentioning
confidence: 99%
“…Evidence from earlier studies, all from Europe or the United States, has been mixed. Some studies have shown violation of these assumptions (27, 28), while others have shown adherence to these assumptions (9, 20, 21). The lack of adherence to assumptions in our study could be because individuals or groups of individuals understood vignettes differently and/or used different thresholds in rating vignettes and their own disability in mobility and cognition.…”
Section: Discussionmentioning
confidence: 99%